2017
DOI: 10.4314/rejhs.v5i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of sedentary lifestyle among bankers in Abuja, North-Central Ngeria

Abstract: Objective: Appropriate regular physical activity is a major component in preventing the growing global burden of chronic disease and at least 60% of the global population fails to achieve the minimum recommendation of 30 minutes moderate intensity physical activity daily. This study was aimed at assessing the knowledge and practice of sedentary lifestyle among bankers in Bwari Area Council, FCT, Abuja in North-Central Nigeria.Methods: This was a descriptive cross sectional study using self administered questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…The high level of PI observed in this study is worrying, because of its strong association with high cardiovascular mortality [27,28] however, it agrees with the 83.3% prevalence reported among workers in some financial institutions in Accra in 2015 [8]. In a similar study among bankers in Nigeria, Aderibigbe and colleagues observed a 60% prevalence of PI which is lower than what was recorded in the current study [29]. It is important to note that the prevalence of PI in this study was comparable across the five banks studied.…”
Section: Discussionsupporting
confidence: 85%
“…The high level of PI observed in this study is worrying, because of its strong association with high cardiovascular mortality [27,28] however, it agrees with the 83.3% prevalence reported among workers in some financial institutions in Accra in 2015 [8]. In a similar study among bankers in Nigeria, Aderibigbe and colleagues observed a 60% prevalence of PI which is lower than what was recorded in the current study [29]. It is important to note that the prevalence of PI in this study was comparable across the five banks studied.…”
Section: Discussionsupporting
confidence: 85%
“…The high level of physical inactivity observed in this study is worrying, because of its strong association with high cardiovascular mortality [ 25 , 26 ] however, it agrees with the 83.3% prevalence reported among workers in some financial institutions in Accra in 2015 [ 10 ]. In a similar study among bankers in Nigeria, Aderibigbe and colleagues observed a 60% prevalence of physical inactivity which is lower than what was recorded in the current study [ 27 ]. It is important to note that the prevalence of physical inactivity in this study was comparable across the five banks studied.…”
Section: Discussioncontrasting
confidence: 84%
“…29 The knowledge of SB was poor compared to the findings of a study conducted in Abuja, Nigeria. 30 This may be explained by the difference in study populations used in both studies. Also, the difference in educational status between the adolescents in this study and the bankers from the previous study could account for the variation in knowledge.…”
Section: Discussionmentioning
confidence: 99%